2018
DOI: 10.3389/fmicb.2018.00391
|View full text |Cite
|
Sign up to set email alerts
|

The Hemagglutinin-Neuraminidase (HN) Head Domain and the Fusion (F) Protein Stalk Domain of the Parainfluenza Viruses Affect the Specificity of the HN-F Interaction

Abstract: Membrane fusion by the parainfluenza viruses is induced by virus-specific functional interaction between the attachment protein (HN) and the fusion (F) protein. This interaction is thought to be mediated by transient contacts between particular amino acids in the HN stalk domain and those in the F head domain. However, we recently reported that replacement of specified amino acids at or around the dimer interface of the HN head domain remarkably affected the F protein specificity. We then intended to further i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Previous study showed that mutations at positions Asp198 and Arg174 reduced syncytial formation, suggesting that the HN gene plays a pivotal role in NDV-induced syncytial formation [ 21 ]. The interaction of HN and F proteins from the same viral strain is necessary for the most efficient function of receptor recognition and fusogenicity because the HN head domain carries the receptor-binding activities and the HN stalk domain harbors the site that determines the F protein specificity in promoting cell–cell fusion [ 22 , 23 ]. Furthermore, previous study suggested that F and HN cooperatively disturb mitochondrial fusion–fusion homeostasis to enhance mitochondrial biogenesis, synergistically inducing significant syncytia formation accompanied with complete autophagic flux in DF-1 and A549 cells [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous study showed that mutations at positions Asp198 and Arg174 reduced syncytial formation, suggesting that the HN gene plays a pivotal role in NDV-induced syncytial formation [ 21 ]. The interaction of HN and F proteins from the same viral strain is necessary for the most efficient function of receptor recognition and fusogenicity because the HN head domain carries the receptor-binding activities and the HN stalk domain harbors the site that determines the F protein specificity in promoting cell–cell fusion [ 22 , 23 ]. Furthermore, previous study suggested that F and HN cooperatively disturb mitochondrial fusion–fusion homeostasis to enhance mitochondrial biogenesis, synergistically inducing significant syncytia formation accompanied with complete autophagic flux in DF-1 and A549 cells [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Their major antigenic spike glycolproteins, hemagglutinin neuraminidase and fusion protein, are encoded by HN and F genes, respectively, and are dominant targets for humoral immunity found in all parainfluenza viruses [16]. Further, the HN protein comprises neuraminidase and hemagglutinin functions, and facilitates membrane fusion with host cells by interaction with the F protein [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…The HN protein regulates virus-host interactions and has both hemagglutinin and neuraminidase activity (11). In addition, the HN protein affects the F protein's function in mediating membrane fusion with host cells (12). Because of its antigenicity and variability, the HN gene has been the preferred target gene region for the phylogenetic analysis of HPIV3 (13).…”
Section: Introductionmentioning
confidence: 99%